ANALYSIS OF POWER PLANT OPERATIONS TO IMPROVE EFFICIENCY USING ENERGY VALUE STREAM MAPPING (EVSM) AND FAILURE MODE AND EFFECTS ANALYSIS (FMEA) METHODS ON COMBINED CYCLE POWER PLANT UNIT AT PT PLN NUSANTARA POWER UP GRESIK : ANALISA PEMBANGKIT LISTRIK GUNA MENINGKATKAN EFISIENSI MENGGUNAKAN METODE ENERGY VALUE STREAM MAPPING (EVSM) DAN FAILURE MODE AND EFFECTS ANALYSIS (FMEA) PADA UNIT PLTGU DI PT PLN NUSANTARA POWER UP GRESIK - Siti Arifah Nuraini; Joumil Aidil Saifuddin; Yekti Condro Winursito (LPPM Universitas Abdurrab, 2025)
To meet human needs, the government builds power plants with adequate capacity and quantity. In the process of electricity generation does not always run well. This study aims to improve the efficiency of the operational process by minimizing the Heat rate value that occurs in the PLTGU unit using the Energy Value Steam Mapping (EVSM) and Failure Mode And Effects Analysis (FMEA) methods. The results of the study showed that the high heat rate in Gas Turbine 1.1 and Steam turbine was caused by fouling in the Compressor Gas Turbine, Corrosion or material damage to the HP Evaporator HRSG, and leakage in the Steam Turbine condenser. The overall heat rate in the block I generating unit before the repair was 1,432.63 kcal/kwh. Then after the proposed repair projection, it was only 830.63 kcal/kwh. This means that there is a decrease in the heat rate in the operational process of 602.01 kcal/kwh or a percentage of 42.02%.